Working together or pulling apart? : the National Health Service and child protection networks - Lupton, Carol (Policy Press, 2001)
This book examines the contribution of the NHS to the multi-agency and inter-professional child protection process. It examines the roles played by health professionals within child protection and investigates the nature and operation of the central policy community and local provider networks. The book also examines the impact of wider socio-political changes on the operation of the child protection process.